An Analysis of Polysemy of “anding-andingen” Proverb in Karo Language: Problems of Natural Semantic MetaLanguage - Karisma E. Tarigan; Mulyadi Mulyadi (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This article aims at proposing a way to identify polysemy ‘anding-andingen’ or proverb in bahasa karo. The writer has an interest to use proverb or anding-aningen in this study because in proverb contains a lot of semantic meaning. This study was conducted using the descriptive qualitative approach in nature; therefore it only describes the semantic knowledge theory. The results of this study indicate that the element DO may occur either with a subject (Actor) alone with a second (Patient) argument as well (in English, as DO TO). It opened the way for a new semantically-inspired approach to grammar constructions. An analysis of ‘X does this’ as ‘X can say this’ and of ‘A because B’ as if not B, the not A’, the writers admitted that both DO and BECAUSE into the stable of semantic primitives. A similar entailment-like relationship obtains between PEOPLE and SOMEONE, but there is at least one significant syntactic difference, namely, that PEOPLE cannot occur with quantifier ONE.